Examining students' academic motivation for studying programming languages. - Ankora, Carlos; Bolatimi, Stephen Oladagba; Bensah, Lily; Mahama, Francois; Kuadey, Noble Arden; Adu, Adolph Sedem Yaw; Adjei, Laurene (Journal of Computer Assisted Learning, 2023)
Background: The degree to which Computer Science (CS) and Information Communication Technology (ICT) students are motivated to learn greatly impacts their study habits, academic achievement in school and ultimately their job prospects. In recent times, skills in programming languages have become vital in searching for employment. Objective: This study sought to examine the academic motivation of students to study programming languages and their pursuit of job prospects in the software development field. Methods: The study adopted the Academic Motivation Scale (AMS) to measure students' motivation. Data was collected from 244 CS and ICT students at different levels of study at Ho Technical University (HTU) who responded to an online questionnaire. Exploratory factor analysis (EFA), reliability analysis, independent samples t‐test and confirmatory factor analysis (CFA) were conducted using IBM statistical package for social sciences (SPSS) and IBM analysis of moment structure (AMOS), respectively. Results and Conclusions: The results showed no significant difference in students' motivation to study programming languages in the university between those who had prior programming languages and those who had none. Also, the results showed no significant difference in the motivation of students to study programming languages between those with and without working experience. The results showed a significant difference between those who want to and do not want to pursue a career in software development and their study motivation of programming languages. Takeaway: Course instructors should emphasize connections between course goals and future employment opportunities. Lay Description: What is already known about the topic: The degree to which students are motivated to learn greatly impacts their study habits and academic achievement.The Academic Motivation Scale is a key measurement instrument for assessing students' level of motivation. What this paper adds: Students who desire to pursue a career in software development are motivated to study programming languages.Students do not require prior programming language experience to be motivated to study programming languages.Students do not require working experience in the ICT field to be motivated to study programming languages. Implications of study findings for practitioners: The study's findings provide instructors and the management of HEIs insights to develop practical and interactive courses in curricula.Course instructors should emphasize connections between course goals and future employment opportunities.Management should provide incentives to the best students who design innovative software to solve problems.